Desain Sistem Informasi untuk Peminjaman Dokumen di Bidang Hubungan Masyarakat Universitas Islam Negeri Sumatera Utara - Muhammad Raihan Muharam; Fikri Haikal; Ahmad Taufik Al Afkari Siahaan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Public Relations (PR) of the State Islamic University of North Sumatra (UINSU) is a strategic unit that manages various important documents in the institution's administrative and communication activities. However, document loan management in this unit is still done manually, making it vulnerable to data loss, late returns, and difficulty in monitoring document status. This community service research aims to design and implement an integrated web-based document loan information system in the UINSU Public Relations sector. The system was developed using the PHP programming language with a MySQL database, implementing a modern, responsive interface. The system's main features include item/document data management, loan and return recording, and real-time stock monitoring. The results of the community service show that the system is able to improve document management efficiency, reduce recording errors, and make it easier for officers to monitor loan status. This system is expected to become a document asset management model that can be adopted by other units within the UINSU environment.